Numerical simulations of MHD generalized Newtonian fluid flow effects on a stretching sheet in the presence of permeable media: A finite difference-based study - Irshad, Sadia; Majeed, Afraz Hussain; Jahan, Shah; Riaz, Arshad; Eldin, Sayed M.; Shahzad, Hasan (Frontiers in Physics, 2023)
In this study, a Casson-Williamson (CW) nanofluid flows and mass transfer characteristics are explored. Further the velocity slip condition and viscous dissipation affect or taken to examine the changes in mass and heat transfer caused by a stretching surface integrated in a permeable media with heat conversion beneath the effect of magnetic field and a consistent thermal radiation. All of the nonlinear fluids physicochemical characteristics are regarded as massive. It is explored whether the nanofluid concentration is constant. The concentration of the nanofluid is examined in the occurrence of chemical reactions as a consequence of the motion of the nanofluid particles in the system. To begin, a group of nonlinear partial differential equations with boundary conditions are put into consideration as base equation to obtain the required BVP mathematical model. The approximate solution for differential equations was found by using the finite difference method, which also took into account the necessary boundary conditions. The results of the numerical analysis are then represented visually to demonstrate how different governing parameters effect velocity, temperature, and concentration. Although the heat transmission exhibits the reverse manner, the non-Newtonian nanofluid moves more quickly in the nonappearance of a magnetic domain than it does in one. Additionally, as the porosity parameter increased, the rate of heat transmission decreased while the skin friction coefficient increased.